Imagination and Faith as Survival Tactics: A Psychoanalytical Study of All But My Life by Gerda Weissmann Klein - Antony, Chaithanya (Journal of English Language and Literature (ISSN: 2368-2132), 2016)
Gerda Weissmann Klein, the survivor of the Nazi’s genocide, in her autobiography All But My Life narrated how imagination and faith acted as coping mechanisms for survival and how this empowered her mind and body and helped her to live as an immortal spiritual being. She never thought of giving up her hopes and walked ahead through hardships with determination. Thus she survived the torments in Nazi concentration camp, unlike her fellow companions. This paper also focussed attention on major psychological responses shown by individuals when adjusting to loss, ten commonalities of suicide, ‘Coping Skills’ and ‘Applied Relaxation’ techniques, soothing power of music and day dreaming over emotional thoughts. This paper also included the main theoretical aspects suggested by Sigmund Freud, Timothy Williamson, Roy Eugene Davis, Jacques Lacan, Wilfred Bion, Immanuel Kant, Donald Robertson, James Bernard, Arthur Schopenhaur, Erin Buckels, Delroy Paulhus and Daniel Jones, and mentioned briefly the life stories of Napolean Bonaparte, Ethel Muvany and viktor Frankle, similar to that of Gerda’s real life story.